التقويم معيارى المرجع والتقويم محكى المرجع في معالجة نتائج اختبارالطلاب - Opier, Ulfa Mawaddah Ahmad; Mufidah, Nuril; Hanafi, Dewi Chamidah; Mustofa, Saiful (Shaut al Arabiyyah, 2025)
The urgency assessment is carried out in processing student test results. The two forms of assessment carried out by the teacher are the norm reference assessment (NRA) and the benchmark reference assessment (BRA). The purpose of this study is to describe: 1) the application of NRA and BRA in processing student test results; 2) The advantages and disadvantages of NRA and BRA in processing student test results; 3) Differences and similarities between NRA and BRA in processing student test results. The research method used is a qualitative method with a library model. The primary data sources for this research are research journals and e-journals related to NRA and BRA in processing student test results, while the secondary data are books related to NRA and BRA in processing student test results. The results in this study are: 1) NRA is used to compare student success relative to other students, while BRA is used to measure exactly the competencies that determine success. 2) The advantages and disadvantages of NRA-BRA can be seen from the development of student learning outcomes. 3) The difference between NRA and BRA is based on 3 criteria, namely test development, student performance assessment standards and the purpose of the test.